Exploring the clinical and mutational spectrum of MORC2 -associated disorders - Aysylu Murtazina; Eugenii Tatarsky; Iuliia Viakhireva; Artem Borovikov; Alexandra Filatova; Elena Dadali; Nina Demina; Natalia Semenova; Tatiana Markova; Ludmila Bessonova; Dmitrii Subbotin; Bakhytkul Myrzaliyeva; et al. (Journal of Medical Genetics, 2026)
Background Pathogenic missense variants in the MORC2 gene are associated with two distinct disorders: Charcot-Marie-Tooth disease type 2Z (CMT2Z) and the recently described DIGFAN (developmental delay, impaired growth, dysmorphic facies and axonal neuropathy) phenotype, which encompasses a broad range of clinical manifestations that vary significantly between individuals. Methods Clinical and imaging data from 16 patients were collected. Western blot analysis was performed on 10 identified variants in affected patients as well as on two novel variants without clinical data. Those missense variants were introduced into the wild-type vector transfected into HEK293T cells, and western blot analysis was performed to assess protein expression level. Results A total of 11 different missense variants in the MORC2 gene were identified in our cohort, including four novel variants. We demonstrate that early-onset MORC2-associated disorders segregate into two principal neurological phenotypes: a predominantly neuromuscular form and a central nervous system-predominant form. The p.Ser87Leu variant, which defines the neuromuscular cluster, was uniquely characterised by a significant reduction in MORC2 protein levels, distinguishing it mechanistically from other variants. Overall, western blot analysis revealed no statistically significant difference in protein expression levels between variants related to CMT2Z and DIGFAN cases. Conclusion A comparison of our patients with previously reported cases revealed an intriguing trend suggesting a probable dependence of the leading clinical features on specific variants in the MORC2 gene. Further accumulation of patient data is required to determine whether this observation correlates with other specific variants.